2017
DOI: 10.1155/2017/7845358
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine Use for Successful Resolution of Post-ERCP Acute Pancreatitis Abdominal Pain

Abstract: We report a case in which a patient with intractable pain secondary to post-endoscopic retrograde cholangiopancreatography (ERCP) acute pancreatitis is successfully treated with a subanesthetic ketamine infusion. Shortly after ERCP, the patient reported severe stabbing epigastric pain. She exhibited voluntary guarding and tenderness without distension. Amylase and lipase levels were elevated. Pain persisted for hours despite hydromorphone PCA, hydromorphone boluses, fentanyl boluses, and postprocedure anxiolyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“… 18 However, no RCTs have examined ketamine use in this context. Other acute pain conditions outside the perioperative setting in which ketamine has anecdotally been reported to be effective include postendoscopic retrograde cholangiopancreatography pancreatitis pain, 23 renal colic, 24 and exacerbation of central pain from Ehlers-Danlos syndrome. 25 …”
Section: Discussionmentioning
confidence: 99%
“… 18 However, no RCTs have examined ketamine use in this context. Other acute pain conditions outside the perioperative setting in which ketamine has anecdotally been reported to be effective include postendoscopic retrograde cholangiopancreatography pancreatitis pain, 23 renal colic, 24 and exacerbation of central pain from Ehlers-Danlos syndrome. 25 …”
Section: Discussionmentioning
confidence: 99%
“…In a case report of a teenager with severe pain secondary to necrotizing pancreatitis, Mulder et al found that the initiation of ketamine as adjunctive pain management led to a rapid reduction in pain scores by day five of infusion [159]. In another case report of a patient with severe post-ERCP pain secondary to acute pancreatitis, Agerwala et al found that the initiation of ketamine infusion was effective in producing quick and long-lasting analgesia [160].…”
Section: Ketaminementioning
confidence: 99%
“…There are anatomic and clinical indicators of neuropathic pain in patients with chronic pancreatic pain, including pancreatic neuritis, pancreatic neural hypertrophy and hyperplasia, as well as hyperalgesia and allodynia (1). Pediatric neuropathic pain can be successfully treated using N‐methyl‐D‐aspartate (NMDA)‐receptor antagonist medications, such as ketamine (3) and methadone (4), and accordingly, emerging evidence from adults with acute and chronic pancreatic pain can demonstrate a favorable response to ketamine (5,6).…”
mentioning
confidence: 99%